EMPOWERING EFL LEARNERS: THE IMPACT OF DIGITAL LITERACY IN BLENDED ENGLISH LANGUAGE TEACHING METHOD - Hanif, Hanif; Kurniawati, Kurniawati; Rizki, Dini (Berajah Journal, 2024)
Universities worldwide face a pressing challenge: traditional teaching methods may not sufficiently prepare English as a Foreign Language (EFL) students for the rigors of academic English. This study investigates the transformative potential of digital literacy in EFL education through a blended learning approach. Digital literacy, encompassing the skills to effectively navigate, evaluate, and utilize technology for learning purposes, emerges as a promising solution. Employing a mixed-methods research design, this study integrates quantitative data from surveys and qualitative insights from interviews and classroom observations involving EFL university students and instructors. Findings reveal a critical need for enhanced English language proficiency, as evidenced by 72.22% of students scoring below 450 on the English Proficiency Test (EPT). The research underscores that digital literacy significantly enriches EFL instruction within the blended learning framework. By seamlessly integrating traditional and digital teaching methodologies, this approach creates a dynamic and engaging learning environment. However, successful adoption hinges on overcoming challenges and providing continuous support for both students and educators.